The Construction and Analysis of Immune Infiltration and Competing Endogenous RNA Network in Acute Ischemic Stroke - Ma, ZhaoLei; Liu, Chun-Feng; Zhang, Li; Xiang, Ning; Zhang, Yifan; Chu, Lan (Frontiers in Aging Neuroscience, 2022)
Acute ischemic Stroke (AIS) is a common neurological disease that seriously endangers both physical and mental health of human. After AIS, activated immune cells are recruited to the stroke site, where inflammatory mediators are released locally, and severe immune inflammatory reactions occur within a short time, which affects the progress and prognosis of IS. Circular RNA (circRNA) is a type of non-coding RNA with a closed loop structure and high stability. Studies have found that circRNA can affect the course of IS. However, there is no report on ceRNA’s pathogenesis in AIS that is mediated by circRNA. In this study, the Cibersort algorithm was used to analyze the distribution of immune cells in patients with AIS. mRNA data set was downloaded from GEO database, WGCNA was used to construct weighted gene co-expression to determine 668 target genes, using GO, KEGG enrichment analysis, construction of PPI network analysis and MCODE plug-in analysis respectively. The results showed that the biological function of the target gene was in line with the activation and immune regulation of neutrophils; signal pathways were mostly enriched in immune inflammation-related pathways. Venn diagram was used to obtain 52 intersection genes between target genes and disease genes. By analyzing the correlation between the intersection genes and immune cells, we found that the top 5 hub genes were TOM1, STAT3, RAB3D, MDM2, FOS, which were all significantly positive correlated with neutrophils while significantly negative correlated with eosinophils. 52 intersection genes and the related circRNA and miRNA were used as input for Cytoscape software to construct a circRNA-mediated ceRNA competition endogenous network, where a total of 18 circRNAs were found. Further analysis of the correlation between circRNA and immune cells found that 4 circRNAs are positively correlated with neutrophils. Our study shows that circRNA plays a regulatory function in the immune pathogenesis of AIS, which could provide a new idea for AIS research.